2u+5=3+u

Simple and best practice solution for 2u+5=3+u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2u+5=3+u equation:


Simplifying
2u + 5 = 3 + u

Reorder the terms:
5 + 2u = 3 + u

Solving
5 + 2u = 3 + u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-1u' to each side of the equation.
5 + 2u + -1u = 3 + u + -1u

Combine like terms: 2u + -1u = 1u
5 + 1u = 3 + u + -1u

Combine like terms: u + -1u = 0
5 + 1u = 3 + 0
5 + 1u = 3

Add '-5' to each side of the equation.
5 + -5 + 1u = 3 + -5

Combine like terms: 5 + -5 = 0
0 + 1u = 3 + -5
1u = 3 + -5

Combine like terms: 3 + -5 = -2
1u = -2

Divide each side by '1'.
u = -2

Simplifying
u = -2

See similar equations:

| 9-5t=17 | | Y=8-4x-2x^2 | | 2+3(x-5)=5-5(2x+1) | | 3.7x=2.7x+8 | | 3-2(2-x)+x=4x-2(4x+1) | | 2x-(2x+1)=4x+2 | | 8x-(6x-9)+8=43 | | -4(w-7)-(8+7w)=-12w | | 4x+72=7x-6 | | -2(1-x)-4x=4(x-1)-2 | | 36x-18=3x+15+3x | | x^4-3x^2+3=0 | | (y^2+xy)dx+(3xy+x^2)dy=0 | | 63=70-7x | | (x-2)(5x-2)= | | (2cosx-1)(sinx+1)=0 | | (27x^2)-10x+3=0 | | f(x)5-6/7x | | -5x/4=5 | | 3+3x=6-3+15x | | (8t+30)+(-16-2t)=-22 | | (8t+30)+(-16-2t)=22 | | 8x-2x-4=-10 | | 2-(x+4)-(1-x)=2-2(3-x)-x | | 2m+3n=-2 | | 1-(1-x)=4x+2 | | 6(x+2)+x=4-x | | 12y=3+2y+-6 | | 8r-5=r-5 | | 4x+7x-x=11-12x | | 4(v+8)-20=15+v | | 6x-1+x=4-x+2 |

Equations solver categories